PHANTOM PUBLIC ORGANIZATIONS AS A TOOL OF REPRESSION IN THE CENTRAL CHERNOZEM REGION IN THE 1920−1930S - Saran, Aleksandr Yu (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2017)
The author considers thatthe emergence of the phenomenon of phantom organizations in the Central Chernozemregion was connected with the aggravation of the conﬂict between the government and the society in the period of the 1920-1930s in the USSR, when the political power eliminated the active and passive resistance ofthe public. Simultaneously, in order to make repression legal, the law enforcement authorities falsiﬁ ed the presence of non-governmental organizations, relating some of their suspectsto them. Thejudicial or extra-judicial authorities with the same powers on the basis of such fraud passed sentences in which pseudo-participation in phantom organizations was seen as a real fault and the basis for conviction. Thus, phantom organizations became a fact of real life.The author has found out that the phantom-governmental organizations were established by the Central Ofﬁce of the NKVD and simultaneously functioned in the territory of several regions of the country. Such centralization simultaneously solved several problems - the scale of the chimeric affairs gave them more credence than local ideas; inexperienced local investigators got the necessary practice of fabrication of criminal cases in collective work under the direction of the centre; the central governance of the law enforcement authorities got additional tool of control over the activities of regional ofﬁces.